Finite element analysis of the influence of fragment size on biomechanical outcomes of various fixation techniques for posterolateral tibial plateau fractures - Hu, Zhenghui; Xia, Yanze; Shi, Gaolong; Wu, Chenying; Li, Liubing (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveThis study aimed to compare the biomechanical stability of different-sized posterolateral tibial plateau fracture fragments under various internal fixation methods using three-dimensional finite element analysis (FEA) and to evaluate the influence of fragment size on displacement and stress distribution with L-shaped and posterior T-shaped plate fixation.MethodsThree-dimensional FEA models of posterolateral tibial plateau fractures were constructed based on computed tomography (CT) data of an adult tibia. Large and small fracture fragments were simulated, with fixation using an L-shaped plate (large fragment: dual-screw transverse arm fixation; small fragment: single-screw transverse arm fixation) or a posterior T-shaped tibial plate (large fragment: four-screw fixation; small fragment: three-screw fixation). Axial loads of 250 N, 500 N, and 750 N were applied to each model. Maximum displacement and maximum von Mises stress of the fixation constructs were recorded and compared under a 750 N load.ResultsUnder a 750 N axial load, FEA revealed: (1) L-shaped plate fixation group: the large-fragment model (dual-screw transverse arm) exhibited a maximum fixation displacement of 0.32 mm and a maximum von Mises stress of 349 MPa, whereas the small-fragment model (single-screw transverse arm) showed a maximum displacement of 0.37 mm and a maximum stress of 454 MPa. (2) Posterior T-shaped plate fixation group: the large-fragment model (four screws) demonstrated a maximum displacement of 0.29 mm and a maximum stress of 189 MPa, while the small-fragment model (three screws) had a maximum displacement of 0.32 mm and a maximum stress of 176 MPa. Overall displacement differences across groups were minimal, and the stress values of all fixation constructs remained below their yield strength, indicating no risk of failure.ConclusionFinite element analysis indicates that fragment size significantly affects the biomechanical stability of internal fixation for posterolateral tibial plateau fractures. For smaller fragments, L-shaped plate fixation with a single-screw transverse arm results in significantly elevated fixation stress. In contrast, posterior T-shaped plate fixation maintains favorable stability and lower stress, even with fewer proximal screws. Thus, for smaller posterolateral tibial plateau fracture fragments, posterior T-shaped plate fixation may represent a biomechanically superior option.